2016
DOI: 10.1016/j.bmc.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

A new motif for inhibitors of geranylgeranyl diphosphate synthase

Abstract: The enzyme geranylgeranyl diphosphate synthase (GGDPS) is believed to receive the substrate farnesyl diphosphate through one lipophilic channel and release the product geranylgeranyl diphosphate through another. Bisphosphonates with two isoprenoid chains positioned on the α-carbon have proven to be effective inhibitors of this enzyme. Now a new motif has been prepared with one isoprenoid chain on the α-carbon, a second included as a phosphonate ester, and the potential for a third at the α-carbon. The pivaloyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Not only has our work demonstrated potential for GGDPS inhibitors as antimyeloma agents (Holstein and Hohl, 2011;Zhou et al, 2014a;Dykstra et al, 2015), but there has also been interest in the use of GGDPS inhibitors as anticancer agents for solid tumors models (Reilly et al, 2016) and in nonmalignant conditions such as pulmonary fibrosis (Osborn-Heaford et al, 2015). Previous efforts to develop GGDPS inhibitors have focused in large part on branched compounds, including V-shaped inhibitors such as DGBP and its analogs as well as more recently U-shaped inhibitors (Wiemer et al, 2007;K-M Chen et al, 2008;Barney et al, 2010;Zhou et al, 2014b;Foust et al, 2016). Prior crystallography studies demonstrated that the V-shaped compounds can occupy both the FDP and the GGDP sites (K- M Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Not only has our work demonstrated potential for GGDPS inhibitors as antimyeloma agents (Holstein and Hohl, 2011;Zhou et al, 2014a;Dykstra et al, 2015), but there has also been interest in the use of GGDPS inhibitors as anticancer agents for solid tumors models (Reilly et al, 2016) and in nonmalignant conditions such as pulmonary fibrosis (Osborn-Heaford et al, 2015). Previous efforts to develop GGDPS inhibitors have focused in large part on branched compounds, including V-shaped inhibitors such as DGBP and its analogs as well as more recently U-shaped inhibitors (Wiemer et al, 2007;K-M Chen et al, 2008;Barney et al, 2010;Zhou et al, 2014b;Foust et al, 2016). Prior crystallography studies demonstrated that the V-shaped compounds can occupy both the FDP and the GGDP sites (K- M Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Crystallography studies revealed that the V-shaped compound occupied the FDP substrate binding site as well as the GGDP product site within the enzyme's active site (K-M Chen et al, 2008). Subsequent efforts focused on modifications of the V-shaped motif (K-M Chen et al, 2008;Barney et al, 2010;Zhou et al, 2014b;Foust et al, 2016). More recently, a series of triazole bisphosphonates were prepared and it was determined that a mixture of geranyl and neryl triazole bisphosphonates (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We already have demonstrated that the Rap1a and ELISA assays give concordant results for GGDPS inhibitors. 9,10,12,29 The HMG-CoA reductase inhibitor lovastatin, which inhibits the synthesis of mevalonate and therefore depletes cells of all isoprenoids downstream of mevalonate, was used as a positive control in these studies. 6 Of the three compounds examined, the bishomoneryl compound 17c most potently disrupted protein geranylgeranylation, with activity seen at a concentration as low as 0.5 μM.…”
Section: Biological Results and Discussionmentioning
confidence: 99%
“…4 Several other dialkyl bisphosphonates have been reported to show comparable activity, 5,6 and similar activity has been found more recently in the closely related ether 4 . 7 While further improvements on the V-shaped motif of these compounds may yet be possible, 8 in our recent efforts 9,10 to secure more potent inhibitors we have examined bisphosphonates assembled through click chemistry. 11,12 In this vein, the most potent inhibitor we have identified to date is the bisphosphonate 5 .…”
mentioning
confidence: 99%